17 Single breath-hold, 3d mdixon pulse sequence for late gadolinium enhancement imaging of ischaemic scar: a feasibility study. (May 2018) - Foley, James RJ; Fent, Graham J; Garg, Pankaj; Broadbent, David; Dobson, Laura E; Chew, Pei G; Brown, Louise AE; Swoboda, Peter P; Plein, Sven; Higgins, David M; Greenwood, John P
Abstract : Introduction: Late gadolinium enhancement (LGE) imaging is well validated for diagnosis and quantification of myocardial infarction (MI). 2D LGE imaging involves multiple breath-holds for acquisition of each short axis slice to cover the left ventricle (LV). 3D LGE methods cover the LV in a single breath hold; breath-hold duration is typically long with images susceptible to motion artefacts. We evaluated a rapid 3D mDIXON pulse sequence for image quality and quantitation of MI. Methods: 92 patients with prior MI underwent identical 1.5 T CMR protocols. Patients underwent conventional 2D PSIR and 3D mDIXON LGE imaging 10 min following contrast administration in random order. Qualitative image assessment and quantitative assessment of myocardial scar mass, scar transmurality were performed. Results: Image quality was comparable between 3D and 2D LGE (1.4±0.6 vs 1.3±0.5; p=0.162). 3D LGE demonstrated greater scar mass (3D: 18.9±17.5 g vs 2D: 17.8±16.2 g p=0.03); this was not statistically significantly different when expressed as %LV mass (3D: 13.4±9.9% vs 2D: 12.7%±9.5% p=0.07). There was significant positive correlation for 3D vs 2D scar mass; Bland-Altman showed mean mass bias of 1.1 g (95% CI: −5.7 to 7.9). Excellent agreement (κ=0.870) between 3D and 2D LGE was seen at segmental analysis of scar transmurality (at threshold of 50% transmural extent). 3D image acquisition was 5% of acquisition time for 2D: 3D (15.6±1.4 s) to 2D (311.6±43.2 s) p<0.0001. Conclusion: Single breath-hold 3D mDIXON LGE imaging allows quantitative assessment of MI and transmurality with comparable image quality in vastly shorter overall acquisition time compared to 2D LGE imaging.